2020
DOI: 10.1016/j.jcorpfin.2020.101585
|View full text |Cite
|
Sign up to set email alerts
|

Access to internal capital, creditor rights and corporate borrowing: Does group affiliation matter?

Abstract: We examine whether the effect of increased creditor rights on corporate borrowing depends on firms' access to internal capital. By exploiting a creditor protection reform in the Indian emerging market, empirical outcomes strongly indicate that strengthening of creditor rights leads to increased corporate borrowing among firms that have constrained access to internal capital compared to business group affiliated firms, which have relatively easier access to internal capital. Further, the increased corporate bor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
9
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 29 publications
(11 citation statements)
references
References 54 publications
2
9
0
Order By: Relevance
“…Aranda-Usón et al (2019) presented the influences of financial resources in businesses on achieving a more advanced circular economy (CE). Thapa et al (2020) presented the differential effects between standalone and business group firms on the credit restructuring of intense creditor liberties that increase credit supply and extend financially constrained firms to achieve higher benefits. Siegrist et al (2020) integrated a conceptual SCF framework with risk management, intangible assets and cost reduction by proficient resource utilization and revenue improvement to highlight how firms could utilize environmental sustainability in their long-term financial decision-making frameworks.…”
Section: Introductionmentioning
confidence: 99%
“…Aranda-Usón et al (2019) presented the influences of financial resources in businesses on achieving a more advanced circular economy (CE). Thapa et al (2020) presented the differential effects between standalone and business group firms on the credit restructuring of intense creditor liberties that increase credit supply and extend financially constrained firms to achieve higher benefits. Siegrist et al (2020) integrated a conceptual SCF framework with risk management, intangible assets and cost reduction by proficient resource utilization and revenue improvement to highlight how firms could utilize environmental sustainability in their long-term financial decision-making frameworks.…”
Section: Introductionmentioning
confidence: 99%
“…Even, Almeida et al (2015) indicated in their study based on Korean business groups that internal capital market helps their affiliated firms in absorbing the negative effect of the Asian crisis on investment. Internal capital market of groups can safeguard their affiliated firms in times when these firms face external financing shocks (Thapa et al, 2020) But, a negative image of the group can act as an obstacle for affiliated firms in arranging funds from financial institutions (Wasiuzzaman et al, 2020). Additionally, the group's overall risk may also act as a deciding factor in arranging outside finances for their affiliated firms.…”
Section: Group Affiliation and Financial Constraintsmentioning
confidence: 99%
“…Additionally, the group's overall risk may also act as a deciding factor in arranging outside finances for their affiliated firms. Based on the above facts, it is debatable whether group affiliation reduces or enhances the financial constraints of their affiliated firms (Buchuk et al, 2014;Almieda et al, 2015;Lou et al, 2019;Wasiuzzaman et al, 2020;Thapa et al, 2020;Ren et al, 2021).…”
Section: Group Affiliation and Financial Constraintsmentioning
confidence: 99%
“…8 However, other empirical studies such as Acharya and Subramanian (2009) and Acharya et al (2011) show that stronger creditor rights could have an adverse effect by reducing firms' risk-taking and investment into innovation. Acknowledging the apparently opposite views on the effects of creditor rights on firm lending and investment, Thapa et al (2020) examine the role of firm's access to internal capital, an important firm characteristic, as a conditioning factor for the effects of creditor rights.…”
Section: Related Literaturementioning
confidence: 99%